DEVELOPING TASK-BASED ENGLISH MODULE FOR SECRETARY STUDENTS: - - Annisa Nur Fatimah (ELT-Lectura, 2019)
The secretary students of the college in which this research conducted use Buku Pegangan Kuliah (BPK) as learning resource of English subject. Nevertheless, according to the result of analysis, the book does not cover the criteria of a good book yet that are analyzed from seven aspects including objective, content, language skill, task, topic, methodology, and presentation. The materials which are presented in the book refer to general English and tend to emphasize on grammar. However, the secretary students need specific English material that focuses on the field. This study is aimed to (1) analyze the relevancy of the existing English textbook with the students’ need; (2) describe the development of task-based English module for secretary department; (3) describe the validity of the module. This study is a research and development, which the main step is conducted in two ways. First, exploration includes library research and field research. Second, development includes product specification planning, product design, expert validation, and tryout. The specific English module is validated by an expert of teaching and learning English and an expert of secretary and office administration. The findings of the study are: (1) the materials of the existing book does not fulfill the secretary students’ need yet; (2) designing task based English module for secretary students based on the data from need analysis; (3) the result of module validation from the two experts obtains 87%, it belongs to valid and feasible to be implemented in the teaching and learning. Keywords: R n D, ESP, English for secretary, need analysis, task based learning